2022
DOI: 10.3390/ijerph192215374
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Yoga-Based Mindfulness Intervention versus Psycho-Educational Session for Older Adults with Mild Cognitive Impairment: The Protocol of a Randomized Controlled Trial

Abstract: Background: There is a global agreement in the medical community that a significant proportion of dementia cases could be prevented or postponed. One of the factors behind this agreement comes from scientific evidence showing that mind-body interventions such as mindfulness and yoga for the elderly have been related to a range of positive outcomes, including improved cognition performance in seniors with mild cognitive impairment (MCI). Objective: This study aims to evaluate the effectiveness of a yoga-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…Future research needs to continue to test the efficacy of these interventions on diverse populations. For example, randomized controlled trials are currently ongoing with elderly populations who experience mild cognitive impairment in Chile (Farhang et al, 2022).…”
Section: Appropriateness Ethics and Multicultural Considerationsmentioning
confidence: 99%

Mindfulness and Yoga

Arrastia-Chisholm,
Adams,
Cakmakci
et al. 2024
Int. J. PWB
“…Future research needs to continue to test the efficacy of these interventions on diverse populations. For example, randomized controlled trials are currently ongoing with elderly populations who experience mild cognitive impairment in Chile (Farhang et al, 2022).…”
Section: Appropriateness Ethics and Multicultural Considerationsmentioning
confidence: 99%

Mindfulness and Yoga

Arrastia-Chisholm,
Adams,
Cakmakci
et al. 2024
Int. J. PWB
“…Baklouti, et al (2022), conducted a cross-sectional study on the effects of hatha yoga on the cognitive functions of the elderly, the main objective was to investigate the effects of hatha yoga on the cognitive functions of the elderly, and had two research groups, it was concluded that hatha yoga in the long term generate better cognitive skills in those who practice it, Unlike those who made up the control group, it is necessary to be able to examine more physiological and psychological variables to highlight the correlation between yoga and cognitive performance [12]. In the study conducted by Farhang et al, (2022), the purpose of the study was to evaluate the effectiveness of a mindfulness intervention based on the practice of yoga (YBM), an individual randomized controlled trial (RCT) was carried out, as results of the study it has been possible to adapt and design the intervention protocol, the evaluation has allowed to examine the effects of a mindfulness intervention based on yoga that allows to improve the functions cognitive and physical of older adults diagnosed with mild cognitive impairment [13]. Zhang et al, (2018), conducted research to demonstrate mind-body effects on cognitive performance of the elderly: a systematic review and meta-analysis.…”
Section: Background Motivation and Objectivementioning
confidence: 99%
“…Promising interventions are mindfulness-based interventions (MBIs), which, as opposed to mere cognitive training, improve moment-to-moment attention control while simultaneously [ 20 , 21 , 22 , 23 , 24 , 25 ] reducing distractions due to internal and external interruptions. The other benefits of these meditation or mindfulness practices are a reduction in stress and an improvement in mood, quality of life, and socio-emotional and cognitive balance in general [ 23 , 26 ].…”
Section: Introductionmentioning
confidence: 99%